Nanofluid containing metal sulfide quantum dots as well as preparation method and application of nanofluid

A nanofluid with metal sulfide quantum dots, prepared using an ionic liquid solvent, addresses dispersion stability issues in lubricating oils, offering enhanced lubrication performance and wear resistance through a one-step solvothermal method.

CN119193213APending Publication Date: 2024-12-27BAOJI UNIV OF ARTS & SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411324145.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing lubricating oils face challenges with poor dispersion stability of nanoparticles, leading to sedimentation and complex, costly preparation processes, and inadequate performance under extreme conditions, resulting in severe friction and wear.

Method used

A nanofluid containing metal sulfide quantum dots is prepared in situ using an ionic liquid as a reaction solvent through a one-step solvothermal method, forming a homogeneous nanofluid with chemical bonds between the ionic liquid and metal sulfide quantum dots, enhancing dispersion stability and lubricating performance.

Benefits of technology

The nanofluid exhibits excellent anti-friction and anti-wear properties with a simple preparation process, improving lubrication performance and stability under extreme conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193213A_ABST
    Figure CN119193213A_ABST
Patent Text Reader

Abstract

The invention provides a nanofluid containing metal sulfide quantum dots as well as a preparation method and application of the nanofluid, the metal sulfide quantum dot nanofluid is generated in situ by taking ionic liquid as a reaction solvent, and the metal sulfide quantum dots are dissolved in the ionic liquid. The preparation method comprises the following steps: preparing ionic liquid, taking a metal source and a sulfur source, preparing a nanofluid crude product through a solvothermal method one-step reaction, and purifying. The nanofluid containing the metal sulfide quantum dots is applied as a lubricating material. According to the nanofluid, the metal sulfide nanomaterial can be dissolved in an ionic liquid system in a quantum dot mode, the dispersion stability problem of the nanomaterial in lubricating oil is solved, meanwhile, an effective lubricating film is formed on the surface of a friction pair in the friction process, the excellent friction reduction and wear resistance effects are achieved, the preparation method is simple, and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lubricants, and in particular to a nanofluid containing metal sulfide quantum dots, and a preparation method and application thereof. Background Art

[0002] Global energy consumption continues to maintain a rapid development trend. 1 / 3-1 / 2 of the energy in mechanical systems is wasted on various forms of friction, and friction also causes serious surface corrosion and environmental pollution. However, the methods used in industry to combat wear include surface strengthening of materials, that is, spraying, surfacing, surface deposition, etc. on the surface of materials. These methods are undoubtedly time-consuming and labor-intensive, and the cost is relatively high. Moreover, it is difficult to perform the above operations in the gaps of industrial parts. Therefore, it is urgent to find a method that is easy to use, has strong anti-wear ability and saves costs. The development of lubricating oil has given hope to solve such problems. Liquid lubricants reduce friction by preventing the sliding interface of metal-to-metal contact and by forming a low-shear, high-durability fluid dynamic and / or elastic fluid dynamic lubricating film on the friction surface. However, when the mechanical system is in the start-stop stage and / or under various extreme conditions, the lubricating film is unstable or even destroyed, resulting in direct contact of the friction surface, thereby generating boundary lubrication and mixed lubrication states, under which severe friction and wear are likely to occur. The additives in the lubricant can form a highly protective boundary film on the friction surface under these conditions, and the performance of the additive greatly affects the tribological properties of the lubricant.

[0003] Although lubricating oil additives show excellent anti-wear performance, their use and performance are often affected by dispersion stability. In view of this, domestic and foreign researchers have conducted a lot of research, but most of them are through surface modification of added nanoparticles, that is, grafting characteristic functional groups to achieve the effect of enhancing dispersion stability. However, the effect of enhancing dispersion stability is not very obvious. Nanofluids have attracted much attention as a hot research topic in recent years. Nanofluids are stable suspensions in base fluids with good physical and chemical properties and fluidity, among which the most notable feature is good dispersion stability. Therefore, using them as lubricating oil additives can improve the problem of low dispersion stability of traditional lubricating oil additives to the greatest extent. The preparation of nanofluids can be divided into physical and chemical methods. The physical method is to use surfactants to improve the stability of nanoparticles in the base fluid, and then use ultrasonic oscillation, magnetic stirrer, high shear mixing, and stirrer to fully ultrasonically mix them to prepare nanofluids. Although the dispersion stability of nanofluids prepared by this method is much better than that of traditional lubricating oil additives, sedimentation still occurs. The chemical method is to chemically combine and coat nanoparticles and then disperse them, which can greatly increase their dispersion stability. Although the nanofluid prepared by this method has good dispersion stability, its process is complicated, purification is difficult, and the preparation cost is too high. It is understood that there are not many studies on this issue at home and abroad, which shows that there is a need to study this issue.

[0004] CN115637188B discloses a nanofluid lubricant, characterized in that, calculated by mass percentage, it includes 0.01-0.15wt% supramolecular gel factor, 0.72-1.08wt% cosolvent, 0.02-0.5wt% modified nanomaterial and 98.75-99.25wt% base oil; the supramolecular gel factor is sodium dodecyl sulfate; the cosolvent includes one or more of oleic acid, linoleic acid, linolenic acid, and palmitoleic acid; the modified nanomaterial includes nanomaterials and surface modifiers for modifying nanomaterials; the nanomaterials include any one or more of metal, metal oxide, sulfide, nitride, polymer, ceramic-based, rare earth-based, and carbon-based nanomaterials; the surface modifier is a saturated or monounsaturated alkyl long chain; the carbon chain length of the surface modifier is within 6 carbon atoms of the single carbon chain length of the supramolecular gel factor. In essence, the nanomaterial is modified by using a surfactant to achieve a high dispersion effect, and the preparation process of the nanofluid is relatively complicated.

[0005] In view of these shortcomings, we considered introducing ionic liquid systems into the preparation process of nanofluids. Ionic liquids have been a hot topic of research in recent years. They have very high stability and strong controllability. The molecular structure of ionic liquids can be customized through design, thereby achieving the regulation of their physical properties and application performance. Therefore, we can design an ionic liquid with strong binding force with nanoparticles, combine nanoparticles into the solution system through chemical reactions to prepare nanofluids, and largely solve the dispersion stability problem of nanoparticles added to lubricating oils. Summary of the invention

[0006] The present application provides a nanofluid containing metal sulfide quantum dots and a preparation method and application thereof, in order to solve the above-mentioned problems mentioned in the background technology.

[0007] The present application provides a nanofluid containing metal sulfide quantum dots. The metal sulfide quantum dot nanofluid is generated in situ using an ionic liquid as a reaction solvent. The nanofluid consists of an ionic liquid and metal sulfide quantum dots, and the metal sulfide quantum dots are dissolved in the ionic liquid.

[0008] Optionally, the general structural formula of the ionic liquid is A + B - , where A + is the ethanolamine cation, B - It is a fatty acid anion.

[0009] Optionally, the fatty acid anion includes a long-chain saturated or unsaturated fatty acid anion, the carbon number of the fatty acid anion is 10-18, and the number of unsaturated double bonds of the unsaturated fatty acid anion is 1-3.

[0010] Optionally, the fatty acid anion is any one of an oleic acid anion, a linoleic acid anion, a capric acid anion, a dodecanoic acid anion, a myristic acid anion, a hexadecanoic acid anion, and an octadecanoic acid anion.

[0011] Optionally, the ethanolamine cation is derived from any one of ethanolamine, diethanolamine, and triethanolamine.

[0012] A method for preparing a nanofluid containing metal sulfide quantum dots, which is used to prepare the above-mentioned nanofluid containing metal sulfide quantum dots, comprises the following steps:

[0013] (1) Preparation of ionic liquid: weigh the ethanolamine cation and fatty acid anion in the ionic liquid in a molar ratio of 1:1, stir at room temperature for 2-12 hours to obtain an ionic liquid, which is used as a reaction solvent;

[0014] (2) taking a metal source and a sulfur source: weighing a metal source and a sulfur source for synthesizing metal sulfide quantum dots, wherein the molar ratio of the metal source to the sulfur source is 1:4, and the weight ratio of the metal source to the ionic liquid is 0.0068-0.027:1;

[0015] (3) Preparation of crude nanofluid: adding ionic liquid, metal source and sulfur source into a high-pressure reactor, and ensuring that the high-pressure reactor is in a closed environment, reacting, and naturally cooling to room temperature to obtain a crude nanofluid containing metal sulfide quantum dots;

[0016] (4) Purification: The crude nanofluid containing metal sulfide quantum dots is dissolved in an organic solvent, filtered once to obtain a transparent solution, a desiccant is added to the transparent solution, and after 5-10 minutes, the solution is filtered a second time. The organic solvent is then removed from the dried transparent solution by a rotary evaporator at 35-60°C, and the solution is further pumped dry by an oil pump to obtain a viscous fluid, i.e., the nanofluid containing metal sulfide quantum dots.

[0017] Optionally, the sulfur source is selected from any one of thiourea, thioacetamide, cysteine, and potassium thiocyanate.

[0018] Optionally, the metal source is selected from any one of Fe, Co, Ni, Cu, Mo, and Zn.

[0019] Optionally, the organic solvent is selected from one or more of petroleum ether, ethyl acetate, ether, acetonitrile, ethanol, acetone, and dichloromethane.

[0020] The invention discloses an application of a nanofluid containing metal sulfide quantum dots. The nanofluid containing metal sulfide quantum dots is the above-mentioned nanofluid containing metal sulfide quantum dots, or the nanofluid containing metal sulfide quantum dots prepared by the above-mentioned preparation method. The nanofluid containing metal sulfide quantum dots is used as a lubricating material.

[0021] The nanofluid containing metal sulfide quantum dots and the preparation method and application thereof provided in the present application realize the preparation of the nanofluid containing metal sulfide quantum dots, and have the following beneficial effects compared with the prior art:

[0022] (1) The nanofluid provided by the present application is composed of an ionic liquid and metal sulfide quantum dots, and the nanofluid uses the ionic liquid as a reaction solvent, and generates a nanofluid containing metal sulfide quantum dots in situ through a one-step reaction by a solvothermal method, thereby overcoming the problem of complex procedures for preparing traditional nanofluids. At the same time, in the process of generating the nanofluid through a one-step reaction, a chemical bond is generated between the ionic liquid and the metal sulfide quantum dots, and the metal sulfide quantum dots are introduced into the molecular structure of the ionic liquid, so that the metal sulfide quantum dots are dissolved in the ionic liquid to form a homogeneous nanofluid. The present application obtains a nanofluid through a one-step reaction by a solvothermal method, which largely solves the problem of poor stability of nanoparticles dispersed in ionic liquids.

[0023] (2) By using the combination of ionic liquid and metal sulfide quantum dots as the starting point, ethanolamine and fatty acid are reacted by Lewis acid-base coordination to form an ionic liquid. Then, the ionic liquid is used as the reaction solvent, a metal source and a sulfur source are added, and a nanofluid containing metal sulfide quantum dots is generated in situ through a solvothermal reaction. During the reaction, chemical bonds are generated between the ionic liquid and the metal sulfide quantum dots, and the metal sulfide quantum dots are incorporated into the molecular structure of the ionic liquid to form a homogeneous nanofluid.

[0024] (4) The nanofluid containing metal sulfide quantum dots provided in the present application has excellent anti-friction and anti-wear properties, and the preparation method is simple, the cost is low, and the performance is excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 A morphology diagram of a MoS2 dispersed sample and a MoS2 quantum dot nanofluid provided in one embodiment of the present application;

[0027] Figure 2 This is a structural analysis diagram of MoS2 quantum dot nanofluid provided in one embodiment of the present application;

[0028] Figure 3 TEM image of MoS2 quantum dot nanofluid provided in one embodiment of the present application;

[0029] Figure 4 A graph showing the change in viscosity of a MoS2 quantum dot nanofluid as a function of shear rate provided in one embodiment of the present application;

[0030] Figure 5A friction coefficient diagram of a MoS2 quantum dot nanofluid as a lubricating additive provided in an embodiment of the present application;

[0031] Figure 6 This is a diagram of the average wear volume of MoS2 quantum dot nanofluid used as a lubricating additive provided in one embodiment of the present application. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present application.

[0033] On the one hand, the present application provides a nanofluid containing metal sulfide quantum dots, wherein the metal sulfide quantum dot nanofluid is generated in situ using an ionic liquid as a reaction solvent, the nanofluid is composed of an ionic liquid and metal sulfide quantum dots, and the metal sulfide quantum dots are dissolved in the ionic liquid.

[0034] Specifically, the nanofluid provided by the present application is composed of an ionic liquid and metal sulfide quantum dots, and the nanofluid uses the ionic liquid as a reaction solvent, and generates a nanofluid containing metal sulfide quantum dots in situ through a one-step reaction by a solvothermal method, thereby overcoming the problem of complex procedures for preparing traditional nanofluids. At the same time, in the process of generating the nanofluid through a one-step reaction, a chemical bond is generated between the ionic liquid and the metal sulfide quantum dots. At the same time, the particle size of the metal sulfide quantum dots of the present application is between 2-5nm, and the particle size is very small. The metal sulfide quantum dots are introduced into the molecular structure of the ionic liquid, so that the metal sulfide quantum dots are dissolved in the ionic liquid to form a homogeneous nanofluid. Compared with the nanofluid formed by physically dispersing nanoparticles in a base oil in the prior art, the present application uses an ionic liquid as a reaction solvent, and obtains a homogeneous nanofluid through a one-step reaction by a solvothermal method, thereby solving the problem of poor stability of nanoparticles dispersed in an ionic liquid.

[0035] Optionally, the general structural formula of the ionic liquid is A + B - , where A + is the ethanolamine cation, B - It is a fatty acid anion.

[0036] Specifically, the cation of the ionic liquid is an ethanolamine cation, and the anion is a fatty acid anion. The ionic liquid as a reaction solvent has the characteristics of low melting point and high stability, which is conducive to the generation of nanofluids. In addition, the alcoholic hydroxyl group in the ethanolamine cation is conducive to the combination of the ionic liquid and the friction pair surface, and the carboxyl group in the fatty acid anion is also easy to adsorb on the friction pair surface. At the same time, the alcoholic hydroxyl group and the metal sulfide quantum dots are chemically bonded, so that the metal sulfide quantum dots are combined into the ionic liquid molecular structure, which is conducive to the combination of the nanofluid and the friction pair surface. The ionic liquid itself has a lubricating effect, which further improves the lubricating performance of the nanofluid.

[0037] Optionally, the fatty acid anion includes a long-chain saturated or unsaturated fatty acid anion, the carbon number of the fatty acid anion is 10-18, and the number of unsaturated double bonds of the unsaturated fatty acid anion is 1-3.

[0038] Optionally, the fatty acid anion is any one of an oleic acid anion, a linoleic acid anion, a capric acid anion, a dodecanoic acid anion, a myristic acid anion, a hexadecanoic acid anion, and an octadecanoic acid anion.

[0039] Optionally, the ethanolamine cation is derived from any one of ethanolamine, diethanolamine, and triethanolamine.

[0040] Specifically, ethanolamine and fatty acid are reacted by acid-base neutralization to obtain the ionic liquid of the present application. The alcoholic hydroxyl group in the ethanolamine cation has high activity, which is conducive to the combination with the metal sulfide quantum dots in the process of generating metal sulfide quantum dots by one-step reaction, so that the metal sulfide quantum dots are dissolved in the ionic liquid structure, which is helpful to obtain a homogeneous nanofluid. At the same time, the alcoholic hydroxyl group in the ethanolamine cation is easy to combine with the friction pair, which is helpful to improve the adsorption stability of the nanofluid on the friction pair surface, and then help to improve the lubrication performance of the nanofluid.

[0041] Preferably, the ethanolamine cation of the present application comes from triethanolamine. When reacting with an alkyl acid, triethanolamine provides a lone pair of electrons to form a coordination bond with the electron-deficient part of the alkyl acid through Lewis acid-base coordination.

[0042] On the other hand, the present application provides a method for preparing a nanofluid containing metal sulfide quantum dots, which is used to prepare the above-mentioned nanofluid containing metal sulfide quantum dots, and the preparation method comprises the following steps:

[0043] (1) Preparation of ionic liquid: weigh the ethanolamine cation and fatty acid anion in the ionic liquid in a molar ratio of 1:1, stir at room temperature for 2-12 hours to obtain an ionic liquid, which is used as a reaction solvent;

[0044] Specifically, during the preparation of ionic liquids, ethanolamine and fatty acid anions are mixed at room temperature and generated through Lewis acid-base coordination. The nitrogen atom in ethanolamine provides a pair of lone electrons to form a coordination bond with the electron-deficient atomic group or ion in the fatty carboxylic acid. Therefore, the molar ratio of ethanolamine cation to fatty acid anion is 1:1. Stirring helps to increase the reaction rate.

[0045] (2) taking a metal source and a sulfur source: weighing a metal source and a sulfur source for synthesizing metal sulfide quantum dots, wherein the molar ratio of the metal source to the sulfur source is 1:4, and the weight ratio of the metal source to the ionic liquid is 0.0068-0.027:1;

[0046] Specifically, the molar ratio of the metal source to the sulfur source is controlled to be 1:4 to ensure the generation of metal sulfide quantum dots. If the molar ratio of the metal source to the sulfur source is too large, the generated nanofluid will contain excessive metal salts, increasing the complexity of the subsequent impurity removal process. The molar ratio of the ethanolamine cation to the sulfur source is limited to control the concentration of the metal sulfide quantum dots in the ionic liquid to avoid excessive concentration leading to excessive concentration of the metal sulfide quantum dots, which cannot be well dissolved in the ionic liquid structure, or too low concentration of the metal sulfide quantum dots, which does not significantly improve the lubricity of the matrix.

[0047] (3) Preparation of crude nanofluid: adding ionic liquid, metal source and sulfur source into a high-pressure reactor, and ensuring that the high-pressure reactor is in a closed environment, reacting, and naturally cooling to room temperature to obtain a crude nanofluid containing metal sulfide quantum dots;

[0048] Specifically, an ionic liquid is used as a reaction solvent, a metal source and a sulfur source are added, the high-pressure reactor is kept airtight, and the reaction is carried out at a temperature of 180°C for 24 hours. After naturally cooling to room temperature, an oily viscous substance is obtained, which is a crude ionic liquid nanofluid. As a reaction solvent, the ionic liquid has good thermal and chemical stability, a wide operating temperature range, and good solubility for the added metal source and sulfur source, which is conducive to the generation of nanofluids.

[0049] (4) Purification: The crude nanofluid containing metal sulfide quantum dots is dissolved in an organic solvent, filtered once to obtain a transparent solution, a desiccant is added to the transparent solution, and after 5-10 minutes, the solution is filtered a second time. The organic solvent is then removed from the dried transparent solution by a rotary evaporator at 35-60°C, and the solution is further pumped dry by an oil pump to obtain a viscous fluid, i.e., the nanofluid containing metal sulfide quantum dots.

[0050] Specifically, the crude nanofluid is added to an organic solvent so that the nanofluid is dissolved in the organic solvent, and a small amount or trace amount of solid impurities contained therein, such as excess metal sulfide, metal source, and sulfur source, are separated from the product nanofluid by filtering to obtain a transparent solution. Then, a desiccant is added to the transparent solution to adsorb water in the transparent solution to achieve the purpose of drying. A large amount of organic solvent is then removed by rotary evaporation, and finally the organic solvent is further drained by an oil pump to obtain a nanofluid containing metal sulfide quantum dots.

[0051] The desiccant is one of anhydrous calcium chloride, anhydrous magnesium sulfate, anhydrous sodium sulfate and anhydrous potassium carbonate, and the weight volume ratio of the nanofluid to the organic solvent is 1g:15-20mL. The process of removing the organic solvent by rotary evaporation is a common and mature impurity removal method in the art. Those skilled in the art are capable of adjusting the parameters of the rotary evaporator according to the actual solvent to be evaporated, which will not be described in detail here.

[0052] The present application realizes the preparation of nanofluids containing metal sulfide quantum dots through the above scheme. By using the combination of ionic liquid and metal sulfide quantum dots as the entry point, ethanolamine and fatty acid are formed into ionic liquids through Lewis acid-base coordination. Then, the ionic liquid is used as the reaction solvent, a metal source and a sulfur source are added, and a nanofluid containing metal sulfide quantum dots is generated in situ through a one-step reaction by a solvothermal method. During the reaction, chemical bonds are generated between the ionic liquid and the metal sulfide quantum dots, and the metal sulfide quantum dots are incorporated into the molecular structure of the ionic liquid to form a homogeneous nanofluid. The present application not only has a simple preparation method and is easy to operate, but also solves the problem of poor stability of nanoparticles dispersed in ionic liquids.

[0053] Optionally, the sulfur source is selected from any one of thiourea (H2NCSNH2), thioacetamide (CH3CSNH2), cysteine ​​(L-cysteine), and potassium thiocyanate (KSCN).

[0054] Optionally, the metal source is selected from any one of Fe, Co, Ni, Cu, Mo, and Zn.

[0055] Optionally, the organic solvent is selected from one or more of petroleum ether, ethyl acetate, ether, acetonitrile, ethanol, acetone, and dichloromethane.

[0056] The invention discloses an application of a nanofluid containing metal sulfide quantum dots. The nanofluid containing metal sulfide quantum dots is the above-mentioned nanofluid containing metal sulfide quantum dots, or the nanofluid containing metal sulfide quantum dots prepared by the above-mentioned preparation method. The nanofluid containing metal sulfide quantum dots is used as a lubricating material.

[0057] Specifically, the metal sulfide quantum dot-containing nanofluid provided in the present application can be used as a lubricant and a lubricating additive for base oil for lubrication of the substrate surface.

[0058] The metal sulfide quantum dot-containing nanofluid provided by the present application, the metal sulfide quantum dots are uniformly dissolved in the ionic liquid, which is conducive to the in-situ generation of a uniform and continuous nanoparticle lubricating film at the friction interface during the friction process. At the same time, the metal sulfide quantum dots provided by the present invention have a high load-bearing capacity, thereby showing an excellent anti-friction and anti-wear effect. Not only can the anti-friction and anti-wear performance of the lubricating oil be improved, but also the wear surface can be repaired in real time during the friction process, and an effective lubricating film can be formed on the friction pair surface. In addition, the alcohol hydroxyl group and carboxyl group in the ethanolamine cation are easy to combine with the friction pair surface, which helps to improve the adsorption stability of the nanofluid on the friction pair surface, thereby enhancing the stability of the lubricating film, and then helping to improve the lubrication performance of the nanofluid.

[0059] The following are embodiments of the present invention and effect test examples, and the technical scheme and technical effect of the present invention are further described, but the protection scope of the present invention is not limited to these embodiments. Any changes or equivalent substitutions that do not deviate from the concept of the present invention are within the protection scope of the present invention. In addition, those who do not indicate specific technical operation steps or conditions in the embodiments are all carried out according to the technology or conditions described in the general literature in this area or according to the product specification. Those who do not indicate the manufacturer of the reagents or instruments used are all conventional products that can be obtained commercially.

[0060] Example 1

[0061] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0062] (1) Preparation of ionic liquid: triethanolamine and oleic acid were weighed in a molar ratio of 1:1 and stirred at room temperature for 2 h to obtain an ionic liquid, which was used as a reaction solvent.

[0063] (2) Taking a metal source and a sulfur source: Weighing a metal source and a sulfur source for synthesizing metal sulfide quantum dots, the molar ratio of the metal source to the sulfur source is 1:4, and the mass ratio of ammonium molybdate to the ionic liquid is 0.0068:1. The metal source is selected from ammonium molybdate, and the sulfur source is selected from thiourea.

[0064] (3) Preparation of crude nanofluid: Add ionic liquid, metal source and sulfur source into a high-pressure reactor, and ensure that the high-pressure reactor is a closed environment. React at a temperature of 180° C. for 24 hours, and naturally cool to room temperature to obtain a crude nanofluid containing metal sulfide quantum dots.

[0065] (4) Purification: The crude nanofluid containing metal sulfide quantum dots is dissolved in ethyl acetate, filtered once to obtain a transparent solution, a desiccant is added to the transparent solution, and after 5-10 minutes, the solution is filtered twice. The dried transparent solution is then subjected to a rotary evaporator to remove the ethyl acetate at 35-60°C, and finally further pumped dry by an oil pump to obtain a viscous fluid, which is a nanofluid containing molybdenum disulfide quantum dots, denoted as 1Mo@4S.

[0066] The desiccant is anhydrous calcium chloride, and the weight-volume ratio of the nanofluid to the organic solvent is 1 g: 15-20 mL.

[0067] Example 2

[0068] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0069] The difference from Example 1 is that:

[0070] (1) Preparation of ionic liquid: triethanolamine and oleic acid were weighed in a molar ratio of 1:1, and stirred at room temperature for 5 h to obtain an ionic liquid, which was used as a reaction solvent.

[0071] (2) Taking a metal source and a sulfur source: Weighing a metal source and a sulfur source for synthesizing metal sulfide quantum dots, the molar ratio of the metal source to the sulfur source is 2:8, the mass ratio of ammonium molybdate to the ionic liquid is 0.0136:1, and the obtained nanofluid containing molybdenum disulfide quantum dots is recorded as 2Mo@8S.

[0072] Example 3

[0073] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0074] The difference from Example 1 is that:

[0075] (1) Preparation of ionic liquid: triethanolamine and oleic acid were weighed in a molar ratio of 1:1 and stirred at room temperature for 9 h to obtain an ionic liquid, which was used as a reaction solvent.

[0076] (2) Taking a metal source and a sulfur source: Weighing a metal source and a sulfur source for synthesizing metal sulfide quantum dots, the molar ratio of the metal source to the sulfur source is 3:12, the mass ratio of ammonium molybdate to the ionic liquid is 0.0205:1, and the obtained nanofluid containing molybdenum disulfide quantum dots is recorded as 3Mo@12S.

[0077] Example 4

[0078] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0079] The difference from Example 1 is that:

[0080] (1) Preparation of ionic liquid: triethanolamine and oleic acid were weighed in a molar ratio of 1:1 and stirred at room temperature for 12 h to obtain an ionic liquid, which was used as a reaction solvent.

[0081] (2) Taking a metal source and a sulfur source: Weighing a metal source and a sulfur source for synthesizing metal sulfide quantum dots, the molar ratio of the metal source to the sulfur source is 3:12, and the molar ratio of the ethanolamine cation to the sulfur source is 0.027:1. The obtained nanofluid containing molybdenum disulfide quantum dots is recorded as 4Mo@16S.

[0082] Example 5

[0083] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0084] The difference from Example 3 is that:

[0085] (2) Taking a metal source and a sulfur source: Weighing a metal source and a sulfur source for synthesizing metal sulfide quantum dots, the metal source is selected from ammonium molybdate, and the sulfur source is selected from thioacetamide. The obtained nanofluid containing molybdenum disulfide quantum dots is recorded as Mo-TM.

[0086] Example 6

[0087] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0088] Same as Example 3:

[0089] (2) Taking a metal source and a sulfur source: Weigh a metal source and a sulfur source for synthesizing metal sulfide quantum dots, wherein the metal source is selected from ammonium molybdate and the sulfur source is selected from thiourea. The obtained nanofluid containing molybdenum disulfide quantum dots is recorded as Mo-TA (the same method as in Example 3 is used again).

[0090] Example 7

[0091] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0092] The difference from Example 3 is that:

[0093] (2) Taking a metal source and a sulfur source: Weigh a metal source and a sulfur source for synthesizing metal sulfide quantum dots, wherein the metal source is selected from ammonium molybdate and the sulfur source is selected from cysteine. The obtained nanofluid containing molybdenum disulfide quantum dots is recorded as Mo-Cy.

[0094] Example 8

[0095] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0096] The difference from Example 3 is that:

[0097] (2) Taking a metal source and a sulfur source: Weighing a metal source and a sulfur source for synthesizing metal sulfide quantum dots, the metal source is selected from ammonium molybdate, and the sulfur source is selected from potassium thiocyanate. The obtained nanofluid containing molybdenum disulfide quantum dots is recorded as Mo-PT.

[0098] Example 9

[0099] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0100] Same as Example 3:

[0101] (1) Preparation of ionic liquid: triethanolamine and oleic acid were weighed in a molar ratio of 1:1, and stirred at room temperature for 9 hours to obtain an ionic liquid, which was used as a reaction solvent. The obtained nanofluid containing molybdenum disulfide quantum dots was denoted as Mo-TO (the same method as in Example 3 was used again).

[0102] Example 10

[0103] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0104] The difference from Example 3 is that:

[0105] (1) Preparation of ionic liquid: triethanolamine and capric acid were weighed in a molar ratio of 1:1, and stirred at room temperature for 9 hours to obtain an ionic liquid, which was used as a reaction solvent. The obtained nanofluid containing molybdenum disulfide quantum dots was denoted as Mo-TC10.

[0106] Embodiment 11

[0107] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0108] The difference from Example 3 is that:

[0109] (1) Preparation of ionic liquid: triethanolamine and dodecanoic acid were weighed in a molar ratio of 1:1, and stirred at room temperature for 9 hours to obtain an ionic liquid, which was used as a reaction solvent. The obtained nanofluid containing molybdenum disulfide quantum dots was denoted as Mo-TC12.

[0110] Example 12

[0111] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0112] The difference from Example 3 is that:

[0113] (1) Preparation of ionic liquid: triethanolamine and tetradecanoic acid were weighed in a molar ratio of 1:1, and stirred at room temperature for 9 hours to obtain an ionic liquid, which was used as a reaction solvent. The obtained nanofluid containing molybdenum disulfide quantum dots was denoted as Mo-TC14.

[0114] Embodiment 13

[0115] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0116] The difference from Example 3 is that:

[0117] (1) Preparation of ionic liquid: triethanolamine and hexadecanoic acid were weighed in a molar ratio of 1:1, and stirred at room temperature for 9 hours to obtain an ionic liquid, which was used as a reaction solvent. The obtained nanofluid containing molybdenum disulfide quantum dots was denoted as Mo-TC16.

[0118] Embodiment 14

[0119] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0120] The difference from Example 3 is that:

[0121] (1) Preparation of ionic liquid: triethanolamine and octadecanoic acid were weighed in a molar ratio of 1:1, and stirred at room temperature for 9 hours to obtain an ionic liquid, which was used as a reaction solvent. The obtained nanofluid containing molybdenum disulfide quantum dots was denoted as Mo-TC18.

[0122] Embodiment 15

[0123] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0124] The difference from Example 3 is that:

[0125] (2) Taking a metal source and a sulfur source: Weighing a metal source and a sulfur source for synthesizing metal sulfide quantum dots, the metal source is selected from Co, and the sulfur source is selected from thiourea. The obtained nanofluid containing molybdenum disulfide quantum dots is recorded as Co-TO.

[0126] Example 16

[0127] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0128] The difference from Example 3 is that:

[0129] (2) Taking a metal source and a sulfur source: Weighing a metal source and a sulfur source for synthesizing metal sulfide quantum dots, the metal source is selected from Fe, and the sulfur source is selected from thiourea. The obtained nanofluid containing molybdenum disulfide quantum dots is recorded as Fe-TO.

[0130] Embodiment 17

[0131] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0132] The difference from Example 3 is that:

[0133] (2) Taking a metal source and a sulfur source: Weighing a metal source and a sulfur source for synthesizing metal sulfide quantum dots, wherein the metal source is selected from Ni and the sulfur source is selected from thiourea. The obtained nanofluid containing molybdenum disulfide quantum dots is recorded as Ni-TO.

[0134] Embodiment 18

[0135] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0136] The difference from Example 3 is that:

[0137] (2) Taking a metal source and a sulfur source: Weighing a metal source and a sulfur source for synthesizing metal sulfide quantum dots, the metal source is selected from Cu, and the sulfur source is selected from thiourea. The obtained nanofluid containing molybdenum disulfide quantum dots is recorded as Cu-TO.

[0138] Embodiment 19

[0139] A method for preparing a nanofluid containing metal sulfide quantum dots comprises the following steps:

[0140] The difference from Example 3 is that:

[0141] (2) Taking a metal source and a sulfur source: Weighing a metal source and a sulfur source for synthesizing metal sulfide quantum dots, the metal source is selected from Zn, and the sulfur source is selected from thiourea. The obtained nanofluid containing molybdenum disulfide quantum dots is recorded as Zn-TO.

[0142] Experimental Example 1

[0143] Nanofluid morphology observation

[0144] Taking the nanofluid formed by dispersing molybdenum disulfide nanoparticles in an ionic liquid by physical dispersion as a control example, the morphology of the nanofluid (3Mo@12S) containing molybdenum disulfide quantum dots provided by Example 3 was observed and compared.

[0145] MoS2 nanoparticles (particle size 2-5 nm) were taken and MoS2 dispersion was prepared by physical dispersion at the same concentration as that of MoS2 quantum dots in nanofluid in Example 3. The morphology of the two fluids was observed and the following results were obtained: Figure 1 Results shown.

[0146] Figure 1 (a) is the positive morphology of the MoS2 dispersed sample. Figure 1 (b) is a positive morphological diagram of the MoS2 quantum dot nanofluid provided in Example 3, Figure 1 (c) is the inverted morphology of the MoS2 dispersion sample. Figure 1 (d) is an inverted morphology diagram of the MoS2 quantum dot nanofluid provided in Example 3, Figure 1 (e) is the inverted bottom morphology of the MoS2 dispersion sample. Figure 1 (d) is an inverted bottom morphology image of the MoS2 quantum dot nanofluid provided in Example 3.

[0147] Depend on Figure 1 It can be observed that the MoS2 dispersed sample has visible MoS2 particles, and the particles are still distinct. The MoS2 dispersed sample has poor fluidity after inversion, and there is obvious precipitation at the bottom after inversion. However, the MoS2 quantum dot nanofluid provided in Example 3 of the present application shows good fluidity after inversion, and there is no precipitation at the bottom. At the same time, the quantum dots are evenly distributed in the fluid, and no particles are observed. This shows that the nanofluid containing metal sulfide quantum dots provided in the present application has a fluid state, and the fluid is evenly distributed.

[0148] Experimental Example 2

[0149] Nanofluid structure analysis

[0150] The structure of the MoS2 quantum dot nanofluid obtained in Example 9 was detected by Fourier transform infrared spectroscopy (FTIR), and the pure ionic liquid (TO) in Example 3 was used as a control sample to obtain the following: Figure 2 Results shown.

[0151] observe Figure 2 It can be seen that at 1710~1750cm -1 The characteristic absorption peak of C=O stretching vibration appears around 1550-1650cm -1 ) and CO (1015~1143cm -1 ) indicates the successful combination of triethanolamine cation and oleate anion, at 680-720 cm -1 and 1400~1440cm -1 At 2850-2972 cm -1 The strong absorption signal around 3200 cm-1 of MoS2 quantum dot nanofluid (Mo-TO) belongs to the stretching vibration of CH. -1An absorption signal attributable to -OH can be observed on the left and right, while only one peak is observed at this position of TO. This is due to the self-aggregation phenomenon and intermolecular hydrogen bonding when MoS2 quantum dots are not combined. After coordination with MoS2 quantum dots, the self-aggregation phenomenon and intermolecular hydrogen bonding weaken. Therefore, only the absorption peak belonging to -OH can be observed in the Mo-TO spectrum.

[0152] Experimental Example 3

[0153] Nanofluid Surface Morphology Analysis

[0154] The surface morphology of the MoS2 quantum dot nanofluid obtained in Example 3 was detected by transmission electron microscopy (TEM), and the following results were obtained: Figure 3 Results shown.

[0155] observe Figure 3 , as shown in the figure, the scattered black dots marked by circles are MoS2 quantum dots. It can be clearly seen that the MoS2 quantum dots provided by the present application are evenly distributed in the ionic liquid, and the particle size is small, between 2-5nm. This is conducive to introducing metal sulfide quantum dots into the molecular structure of the ionic liquid, so that the metal sulfide quantum dots are dissolved in the ionic liquid to form a homogeneous nanofluid. When used as a lubricating material, it can form a continuous and stable lubricating film on the surface of the friction pair, better isolate the friction pair, and thus achieve a better friction reduction and anti-wear effect.

[0156] Experimental Example 4

[0157] Nanofluid Viscosity Analysis

[0158] The viscosity of the MoS2 quantum dot nanofluid provided by Examples 1 to 4 was tested as a function of shear rate, and compared with the pure ionic liquid (TO) in any one of Examples 1 to 4, and the results were as follows: Figure 4 shown.

[0159] Depend on Figure 4 It can be clearly seen that the MoS2 quantum dot nanofluids provided in Examples 1 to 4 have lower viscosity and better fluidity than the ionic liquid (TO). At the same time, the low shear viscosity of the MoS2 quantum dot nanofluid in Example 3 is higher than that of the other examples, indicating that Example 3 has better anti-settling performance and storage stability.

[0160] Experimental Example 5

[0161] Analysis of tribological properties of nanofluids

[0162] The tribological properties of the nanofluid containing metal sulfide quantum dots provided in Examples 1 to 12 were tested. The test conditions were: load 100N, temperature 25°C, frequency 25Hz, amplitude 1mm, and test time 30min; the upper test ball was a Φ10mm AISI 52100 steel ball; in the steel / steel friction pair, the lower sample was a Φ24mm, 7.9mm thick AISI 52100 steel block with a hardness of 750-850HV; the friction coefficient was measured using an SRV-V micro-vibration friction and wear tester produced by Optimol, Germany, and the wear volume of the lower sample was measured using a BRUKER-NPFLEX three-dimensional optical profiler. Each experiment was repeated at least 3 times and the average value was taken.

[0163] Experimental Example 5.1

[0164] Examples 1 to 4 contain different concentrations of molybdenum disulfide quantum dot nanofluid as a lubricant for tribological performance testing, with ionic liquid (TO) as a control sample. The test results are shown in Table 1.

[0165] Table 1

[0166]

[0167]

[0168] Experimental Example 5.2

[0169] In Examples 5 to 8, the tribological properties of molybdenum disulfide quantum dot nanofluids synthesized using different sulfur sources as lubricants were tested. The test results are shown in Table 2.

[0170] Table 2

[0171] (Steel / Steel Friction Pair) Average friction coefficient <![CDATA[Average wear volume (μm 3 )]]> Mo-TM 0.13 148000 Mo-TA 0.083 83000 Mo-Cy 0.085 95000 Mo-PT 0.090 114000

[0172] Experimental Example 5.3

[0173] In Examples 9 to 14, different fatty acids were used as anion sources of the ionic liquid system to synthesize metal sulfide quantum dot nanofluids for testing the tribological properties of lubricants. The test results are shown in Table 3.

[0174] Table 3

[0175] (Steel / Steel Friction Pair) Average friction coefficient <![CDATA[Average wear volume (μm 3 )]]> Mo-TC10 0.118 154000 Mo-TC12 0.115 135000 Mo-TC14 0.112 118000 Mo-TC16 0.114 124000 Mo-TC18 0.116 139000 Mo-TO 0.108 65000

[0176] Experimental Example 5.4

[0177] In Examples 15 to 19, different metal salts were used as the metal source of the reactants to synthesize metal sulfide quantum dot nanofluids for testing the tribological properties of lubricants. The test results are shown in Table 4.

[0178] Table 4

[0179]

[0180]

[0181] It can be seen from Table 1 that when triethanolamine is used to provide ethanolamine cations and oleic acid is used to provide fatty acid anions in the ionic liquid, and the mass ratio of the added ammonium molybdate to the ionic liquid is 0.0205:1, the obtained nanofluid containing molybdenum disulfide quantum dots (3Mo@12S) has the most obvious improvement in friction reduction and anti-wear performance compared to pure ionic liquid (TO). It can be seen from Tables 1 to 4 that the molybdenum disulfide quantum dot nanofluid provided in the present application has better friction reduction and anti-wear performance than pure ionic liquids, and the improvement in friction reduction performance is better than anti-wear performance. Among them, 3Mo@12S, Mo-TO, and Mo-TA have the same preparation method, but there are differences in friction coefficient and wear volume, which are affected by the fluctuations of multiple factors such as instruments, environment, and friction pairs, but the data are all within the error range.

[0182] Experimental Example 5.5

[0183] The commercially available lubricant SN0-W30 was used as the base oil, and the MoS2 quantum dot nanofluid (Mo-TO) obtained in Example 9 was used as the lubricant additive. Mo-TO was added to the SN0-W30 base oil at different mass concentrations (the mass concentrations of Mo-TO added were: 0.1%, 0.3%, 0.5%, 0.7%, 1%), and ultrasonically treated for 60-180 minutes at a temperature of 40-80°C. At the same time, it was shaken during the ultrasonic process to ensure that the sample was evenly mixed. The tribological properties were tested, and the results were as follows: Figure 5 and Figure 6 shown.

[0184] observe Figure 5 and Figure 6 It was found that adding the MoS2 quantum dot nanofluid provided in this application as a lubricant additive to the SN0-W30 base oil significantly improved the friction reduction and anti-wear properties of the SN0-W30 base oil. And when the addition amount is 0.5%, the tribological performance is optimal. This shows that the addition of nanofluid is conducive to improving the combination of the base oil and the friction pair surface, thereby helping to form a stable and effective lubricating film on the friction pair surface, which not only avoids direct contact between the friction pairs during the friction process, but also can repair the worn surface in real time, thereby enhancing the friction reduction and anti-wear properties of the base oil.

[0185] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A nanofluid containing metal sulfide quantum dots, characterized in that: The metal sulfide quantum dot nanofluid is generated in situ using ionic liquid as a reaction solvent. The nanofluid consists of ionic liquid and metal sulfide quantum dots, and the metal sulfide quantum dots are dissolved in the ionic liquid.

2. The nanofluid containing metal sulfide quantum dots according to claim 1, characterized in that: The general structural formula of the ionic liquid is A + B - , where A + is the ethanolamine cation, B - It is a fatty acid anion.

3. The nanofluid containing metal sulfide quantum dots according to claim 2, characterized in that: The fatty acid anions include long-chain saturated or unsaturated fatty acid anions, the carbon number of the fatty acid anions is 10-18, and the number of unsaturated double bonds of the unsaturated fatty acid anions is 1-3.

4. The nanofluid containing metal sulfide quantum dots according to claim 2, characterized in that: The fatty acid anion is any one of an oleic acid anion, a linoleic acid anion, a capric acid anion, a dodecanoic acid anion, a myristic acid anion, a hexadecanoic acid anion, and an octadecanoic acid anion.

5. The nanofluid containing metal sulfide quantum dots according to claim 2, characterized in that: The ethanolamine cation is derived from any one of ethanolamine, diethanolamine and triethanolamine.

6. A method for preparing a nanofluid containing metal sulfide quantum dots, characterized in that: For preparing the nanofluid containing metal sulfide quantum dots according to any one of claims 1 to 5, the preparation method comprises the following steps: (1) Preparation of ionic liquid: weigh the ethanolamine cation and fatty acid anion in the ionic liquid in a molar ratio of 1:1, stir at room temperature for 2-12 hours to obtain the ionic liquid, which is used as a reaction solvent; (2) taking a metal source and a sulfur source: weighing a metal source and a sulfur source for synthesizing metal sulfide quantum dots, wherein the molar ratio of the metal source to the sulfur source is 1:4, and the weight ratio of the metal source to the ionic liquid is 0.0068-0.027:1; (3) Preparation of a crude nanofluid: adding the ionic liquid, the metal source and the sulfur source into a high-pressure reactor, and ensuring that the high-pressure reactor is in a closed environment, reacting, and naturally cooling to room temperature to obtain a crude nanofluid containing metal sulfide quantum dots; (4) Purification: The crude nanofluid containing metal sulfide quantum dots is dissolved in an organic solvent, filtered once to obtain a transparent solution, a desiccant is added to the transparent solution, and after 5-10 minutes, the transparent solution is filtered twice, and the organic solvent is removed from the dried transparent solution by a rotary evaporator at 35-60° C., and finally further pumped dry by an oil pump to obtain a viscous fluid, i.e., the nanofluid containing metal sulfide quantum dots.

7. The method for preparing a nanofluid containing metal sulfide quantum dots according to claim 6, characterized in that: The sulfur source is selected from any one of thiourea, thioacetamide, cysteine ​​and potassium thiocyanate.

8. The method for preparing a nanofluid containing metal sulfide quantum dots according to claim 6, characterized in that: The metal source is selected from any one of Fe, Co, Ni, Cu, Mo and Zn.

9. The method for preparing a nanofluid containing metal sulfide quantum dots according to claim 6, characterized in that: The organic solvent is selected from one or more of petroleum ether, ethyl acetate, ether, acetonitrile, ethanol, acetone, and dichloromethane.

10. An application of a nanofluid containing metal sulfide quantum dots, characterized in that: The nanofluid containing metal sulfide quantum dots is the nanofluid containing metal sulfide quantum dots as described in any one of claims 1 to 5, or the nanofluid containing metal sulfide quantum dots prepared by the preparation method as described in any one of claims 6 to 9, and the nanofluid containing metal sulfide quantum dots is used as a lubricating material.